Afghan English Major Students’ Attitudes Toward Native-Like Proficiency in the English Language - Hazrat Usman Mashwani; Abdullah Noori (Universitas Muhammadiyah Yogyakarta, 2023)
The term native-like proficiency in English refers to the ability to speak the English language like a native speaker. This study was conducted to investigate Afghan English major undergraduate students’ attitudes toward native-like proficiency in the English language at two public universities in Afghanistan. The study specifically investigated the attitudes of Afghan English major undergraduate students toward the characteristics of a native speaker of the English language, native speakers’ linguistic imperialism, and native-like proficiency in the English language. A mixed research design was used for the study. The quantitative data were descriptively analyzed in terms of frequencies using SPSS and presented in tables. The qualitative data were thematically analyzed and presented. A total of 113 fourth-year (senior students) voluntarily participated in the study. The findings revealed that perfect pronunciation, fluency, and grammatical accuracy were the defining attributes of native speakers. Similarly, students believed that only native speakers have the right to decide the rules or to standardize the English language and that only a native speaker has better English language skills. Moreover, the results revealed that Afghan English major students’ attitudes toward native-like proficiency in the English language were highly positive, and they love to speak with a native-like accent. It is hoped that the current study’s findings will help educators and will be a valuable addition to the current mass of data on the subject.